2014
DOI: 10.3732/apps.1400057
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite primers forCamissoniopsis cheiranthifolia(Onagraceae) and cross‐amplification in related species

Abstract: • Premise of the study: We developed 24 nuclear microsatellite primers from an enriched genomic library for the Pacific coastal dune endemic Camissoniopsis cheiranthifolia to study the consequences of mating system differentiation, the genetics of species’ range limits, and hybridization with its closest sister taxon, C. bistorta.• Methods and Results: Twenty-four primer pairs were developed and characterized in four populations of C. cheiranthifolia and one population of C. bistorta. We also tested eight addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Following guidelines that a sample of 20–30 individuals assayed for 10–20 polymorphic nuclear microsatellites (nSSR) yields reliable estimates of most population genetic parameters (Hale, Burg, & Steeves, ), we genotyped ~25 individuals/population (mean/population = 25.97, total n = 987, Table ) for 13 polymorphic nSSR loci (B11, B34, B59, C19, C49, C67, C89, C110, C133, C135b, E30, E70, E42) following López‐Villalobos, Samis, and Eckert (). We assayed 10% of samples twice to ensure repeatability.…”
Section: Methodsmentioning
confidence: 99%
“…Following guidelines that a sample of 20–30 individuals assayed for 10–20 polymorphic nuclear microsatellites (nSSR) yields reliable estimates of most population genetic parameters (Hale, Burg, & Steeves, ), we genotyped ~25 individuals/population (mean/population = 25.97, total n = 987, Table ) for 13 polymorphic nSSR loci (B11, B34, B59, C19, C49, C67, C89, C110, C133, C135b, E30, E70, E42) following López‐Villalobos, Samis, and Eckert (). We assayed 10% of samples twice to ensure repeatability.…”
Section: Methodsmentioning
confidence: 99%
“…At all sites, we sampled ࣙ500 m from transplant plots to avoid transplant experiment descendants. Each sample was genotyped for 13 polymorphic microsatellite loci following López-Villalobos et al (2014). We quantified within-population genetic diversity using several complementary measures: total number of alleles detected (A), total number of private alleles (A p ), rarefied number of alleles per locus (A r ) using 1000 bootstrap samples of the smallest sample size (n = 20), observed (H o ) and expected heterozygosities (H e ), and the inbreeding coefficient (F) estimated using the R package DiveRsity (v. 1.9.73, Keenan et al 2013).…”
Section: Population Genetic Analysesmentioning
confidence: 99%
“…Moreover, almost all of the populations sampled for this study were located from data on herbarium specimens that had been identified to species. López-Villalobos and Eckert (2018) assayed 805 individuals from 32 mainland populations across the range of C. cheiranthifolia (mean = 25 per population) for variation at 13 nuclear microsatellite markers (nSSR; see methods of López-Villalobos et al, 2014) and a subset of these individuals (124 from 27 populations) for variation at nine polymorphic chloroplast DNA microsatellites (cpSSR; following Weising and Gardner, 1999;Chung and Staub, 2003). We used those data here.…”
Section: Species Identification Sampling Dna Isolation and Genotypingmentioning
confidence: 99%